Enhancing learners’ grammar competence through teacher’s oral and written corrective feedback - Karenia Jannah Dewi Prayogo; Suharyadi Suharyadi; Raihana Binti Romly (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Giving proper corrective feedback is essential for learners in learning English grammar. However, which form of corrective feedback works more effective remains insufficiently explored. This study aims to examine the effect of OCF and WCF on learners' English grammatical ability at a state Islamic junior high school in Malang Indonesia, specifically on the simple past tense. Deploying a quasi-experimental design with two groups: 20 learners of the 7G class as the Experimental Group and 20 learners of the 7I class as the Control Group, this study collected data from the pre-test and post- test. To measure the significant differences between OCF and WCF, the means of the tests of both groups were analyzed using Analysis of Covariance (ANCOVA). This study reveals that OCF and WCF are effective in improving learners' grammar. However, there was no statistically significant difference between the two groups. The OCF group demonstrated slightly greater improvement in gain scores, while the WCF group achieved higher post-test mean scores. These findings suggest that both types of corrective feedback are comparably effective, although they may support different aspects of learning.